Understanding the relationship between social media use for information acquisition and life satisfaction from a knowledge, beliefs, and practices perspective - Sun, Mengru (Frontiers in Psychology, 2025)
BackgroundThe relationship between social media use and subjective well-being is an important research topic. Nevertheless, limited research has specifically explored the role of social media use for information acquisition on life satisfaction. This study investigated how the use of social media for information acquisition influenced life satisfaction by examining a proposed theoretical model.MethodsData were collected online through a survey company. A total of 1,651 individuals responded to the survey invitation via email and participated in the study. Data cleaning was conducted, resulting in a final valid sample of 1,513 cases. In this study, SPSS 22.0 was used to perform descriptive statistics and correlation analysis on the data. The mediation model was tested using the SPSS macro PROCESS (Model 6), with the significance of indirect effects assessed through the bootstrap method.ResultsThe results indicated that social media use for information acquisition exerted both a direct positive effect on life satisfaction and an indirect effect through the sequential mediation of health knowledge and self-efficacy. Notably, only perceived knowledge demonstrated a significant mediating effect, whereas actual knowledge did not. Additionally, self-efficacy significantly mediated the relationship in conjunction with both types of knowledge.ConclusionBy differentiating the roles of perceived and actual knowledge within digital environments, this study extends of the knowledge, beliefs, and practices theory and provides practical implications for health-related interventions.